Perancangan Jaringan Perpipaan Air Bersih dari Sumber Mata Air ke Bak Penampung di Desa Kaduela Kabupaten Kuningan dengan Perangkat Lunak Epanet 2.2 - Nur Rohman, Deni; Sonawan, Hery; Tohasan, Achmad (Universitas Majalengka, 2024)
Clean water is a necessity for every living creature, including humans. The quality and quantity of water greatly influences the development of every living creature. The more rapid human growth and development, the need for water also increases. This research was conducted in Kaduela Village, Kuningan Regency, precisely in Bina Bakti Hamlet. This research aims to solve the problem of clean water availability for the community in Bina Bakti Hamlet. This research was conducted to design a clean water piping network from the spring to the reservoir. The storage tank will be built behind the pavilion and has a capacity of 10,000 liters. Assuming the number of houses is 15 and inhabited by 8 people, so in total there are 15 x 8 = 120 people. The pipe that will be used is a PVC type pipe with a diameter of 3 inches (60 mm) and 2.5 inches (50 mm). The highest pressure was obtained with a value of 35.11 mH2O and the lowest was 10 mH2O. The water speed obtained ranged from 1.05-1.52 m/s. This design was created using Epanet 2.2 software, and was also created as a simulation and analysis that will be used on actual pipe networks. With the hope of helping the community to get access to clean water.